Of Microbes and Men. War and Peace on the Mucosal Surfaces - Philippe Sansonetti (Collège de France, 2013)
Our bodies contain ten times more bacteria than cells and their activity is essential for our organisms. A true symbiosis exists between humans and microbes, the complex mechanisms of which can only be decoded using molecular genetics. However these bacteria can also cause infectious and parasitic diseases which kill over 15 million people a year throughout the world. To develop effective treatments and vaccines for such diseases, scientists need to know how bacteria outmanoeuvre the body's d...